DNA damage response and cell fate decisions across the lifespan: from fetal development to age-related respiratory diseases - Xuewei Cui; Ye Wang; Jianhua Fu (Cell & Bioscience)
Abstract The integrity and stability of DNA, an essential genetic material, need to be maintained for normal cellular function, growth, and development. The DNA damage response (DDR) constitutes a complex, sophisticated, and extensive signaling network that preserves genomic stability under stress. It can be divided into the DNA damage surveillance system and DNA damage repair system, which work in concert to ensure genomic integrity. When DNA damage surpasses the repair capacity of the DDR, unrepaired DNA damage accumulates, inducing cellular senescence and altering the fate of alveolar epithelial cells; this process is intricately linked to the onset, progression, and management of developmental and chronic lung diseases. In this review, recent research on the pathogenic mechanisms of DDR in respiratory diseases across the lifespan, including bronchopulmonary dysplasia, bronchial asthma, chronic obstructive pulmonary disease, and idiopathic pulmonary fibrosis, as well as progress in the development of associated targeted therapeutic strategies, is synthesized.